N-Benzoyl-2-methylbenzenesulfonamide - Suchetan, P. A. (International Union of Crystallography, 2010)
In the title compound, C(14)H(13)NO(3)S, the conformation of the N—H bond in the C—SO(2)—NH—C(O) segment is anti to the C=O bond. The tolyl and benzoyl groups are twisted about the S—N bond, with a C—S—N—C torsion angle of 68.8 (4)°. The dihedral angle between the sulfonyl and the benzoyl benzene rings is 73.9 (1)°. In the crystal, the molecules are linked into C(4) chains along the c axis by N—H⋯O hydrogen bonds.